2017
DOI: 10.1002/art.39852
|View full text |Cite
|
Sign up to set email alerts
|

Gout and Risk of Fracture in Women: A Prospective Cohort Study

Abstract: Objective Uric acid may be linked to bone health through its anti-oxidant or pro-oxidant effects, thereby affecting bone resorption and formation, or through inhibition of vitamin D activation and higher parathyroid hormone level. Prior studies on the relation between uric acid and bone mineral density have demonstrated conflicting results. To date, there are no prospective studies examining the relation between gout, a disease characterized by hyperuricemia and inflammation, and hip or wrist fracture risk in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 71 publications
2
30
1
Order By: Relevance
“…Tzeng et al [23] reported that gout history increased the fracture risk, which was consistent with the results of a Chinese adult-based research conducted by Wang et al [24]. However, the relationship became variable when focus on different fracture sites in the study performed by Paik et al [17], in which the risk of fractures raised in the hip but not in the wrist. Kim et al [25] conducted a large-scale epidemiological study and demonstrated the neutral association between gout and bone health, and Sultan et al [1] reported the similar results in a nationally representative cohort research.…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…Tzeng et al [23] reported that gout history increased the fracture risk, which was consistent with the results of a Chinese adult-based research conducted by Wang et al [24]. However, the relationship became variable when focus on different fracture sites in the study performed by Paik et al [17], in which the risk of fractures raised in the hip but not in the wrist. Kim et al [25] conducted a large-scale epidemiological study and demonstrated the neutral association between gout and bone health, and Sultan et al [1] reported the similar results in a nationally representative cohort research.…”
Section: Introductionsupporting
confidence: 72%
“…After 326 studies excluded by duplicates, 2291 excluded by reading titles and abstracts, and 32 studies were downloaded and carefully checked by reading full texts. After careful reading, five articles [1, 17, 2325] involving eight datasets were considered to be qualified for the quantitative analysis of the association of gout with the risk of fractures, and four articles [1, 23, 26, 28] were considered to be qualified for the quantitative analysis of the association of urate-lowering with the risk of fractures. The inclusion processes and reasons for exclusion were depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6-8 A US-based study 21 reported positive associations between gout and incidence of hip and wrist fracture in women, with an adjusted excess risk of 12% and 38%, respectively. Although this study refutes our findings, it used self-reported information on both gout and fracture, which may have introduced bias.…”
Section: Discussionmentioning
confidence: 99%